Phytotelm to assess bacterial multi-resistance to the antibiotics in a deep tropical forest - Sánchez-Vargas, Stephanny (2022)
Paradoxically, the use of antibiotics has resulted in the proliferation of resistant microorganisms in environments where they were not thought to be likely to appear. In this context, this research aimed to evaluate the phytotelmata as a matrix to detect the presence of bacterial strains with antibiotic resistance in the deep understory of tropical cloud forest and in a nearby rural town. The study was carried out in the Santa Elena Cloud Forest Reserve and the urban zone of the Santa Elena town, only 10 km. A compounded sample of phytotelm water was collected from 10—15 bromeliads and heliconia plants by site. Gram-negative bacterial strains found were evaluated to antibiotic susceptibility tests (13 antibiotics). In both sites, five strains presented multi-resistance to more than three antibiotics. Overall, antibiotics possessing cell wall synthesis inhibitor mechanisms were the most common with resistance for both sites followed by those acting as protein synthesis inhibitors. NMDS and PERMANOVA revealed that both environments had a similar response to antibiotic resistance (P > 0.05). The detection of bacterial multi-resistance to antibiotics in understory phytotelm water could become a quick tool to determine the degree of exposure of natural ecosystems to anthropogenic effects. This research opens the discussion of the potential dangers of the appearance of bacterial antibiotic multi-resistance in natural ecosystems, whose future impact is uncertain.